Assessing the social impact (learning and growth) of agricultural microenterprises In Latakia Province- Syria. (Journal of Hama University, 2024)
The research aimed to evaluate the social impact of micro-agricultural projects in Latakia Province, in terms of awareness and learning, increased job opportunities, and higher income, by determining the extent of social benefit for farmers investing in micro-agricultural projects of all types (plant and animal production, food industries).To achieve the research objectives, a questionnaire was designed and distributed to a random sample of farmers, consisting of 303 projects, which constitute about 10% for plant production and animal production projects, and 20% for food industry projects, out of the total population studied, 2861 projects, in the dependent areas. For Latakia Governorate (Jableh, Al-Haffa, Qardaha, Latakia), efficiency was evaluated using a three-point Likert scale, and some financial and productivity indicators were used.  The results of the research indicated that micro-agricultural projects have an important social impact on farmers, in terms of increasing experience, learning, and awareness. These results also indicated their role in increasing income and increasing job opportunities. These results also highlighted the most important obstacles that projects face, the most important of which is high production costs. Total. The research recommends establishing an agricultural cooperative that includes small farmers in each region, encouraging micro-agricultural investment for every Syrian family, and developing irrigation and fodder cultivation operations.  Keywords: social impact, microenterprises, performance efficiency, evaluation.
Keywords: Keywords: social impact, microenterprises, performance efficiency, evaluation